2017
DOI: 10.1016/j.jbankfin.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Corporate investment and bank-dependent borrowers during the recent financial crisis

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 29 publications
(12 reference statements)
6
51
0
Order By: Relevance
“…Overall, these results are in line with empirical findings by Vermeulen (2002) and the literature on the financial propagation mechanism, which states that large firms tend to be better diversified and are likely to face lower financial constraints (Gertler and Gilchrist, 1994). The results, therefore, provide some preliminary evidence for the importance of bank credit supply restrictions, thereby supporting earlier studies which find that investment by borrowers that are more dependent on banks drops significantly relative to that of borrowers less dependent on banks (Buca and Vermeulen, 2017).…”
Section: The Role Of Firm Size and Sectorssupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, these results are in line with empirical findings by Vermeulen (2002) and the literature on the financial propagation mechanism, which states that large firms tend to be better diversified and are likely to face lower financial constraints (Gertler and Gilchrist, 1994). The results, therefore, provide some preliminary evidence for the importance of bank credit supply restrictions, thereby supporting earlier studies which find that investment by borrowers that are more dependent on banks drops significantly relative to that of borrowers less dependent on banks (Buca and Vermeulen, 2017).…”
Section: The Role Of Firm Size and Sectorssupporting
confidence: 89%
“…Moreover, changes in general risk sentiment may impact on the leverage target through both the supply of and demand for funds (see e.g. Amador and Nagengast, 2016;Buca and Vermeulen, 2017;Cingano et al, 2016;Storz et al, 2017). We will come back to these aspects in the empirical section.…”
Section: Related Literaturementioning
confidence: 99%
“…Like Buca and Vermeulen (2012), we divide the economic cycle into three parts, with downturn, crisis, and upturn. The cyclical dummies are defined as year-on-year changes in sector-level value added.…”
Section: Methodsmentioning
confidence: 99%
“…Barlevy (2007) put forward a theoretical argument accompanied by empirical evidence from the United States that although there is a tendency for procyclical research and development (R&D) to be concentrated in booms, it would be optimal to concentrate R&D in recessions. More recently, Buca and Vermeulen (2012) looked at a sample of European firms and found that profitable investment opportunities have been foregone by bank-dependent firms, which faced credit constraints during the 2009 financial crisis. Ivashina and Scharfstein (2010) and Campello et al (2011) document heavy credit line drawdowns at the onset of the financial crisis due to firms' concern about the ability of banks to provide liquidity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This phenomenon, known as credit crunch, affected the SMEs' capacity to raise the financial resources needed (Canton et al, 2010;Buca and Vermeulen, 2012;Buera et al, 2012;Iyer et al, 2013;Klein, 2014). The evidence commonly found in literature, in fact, agrees in indicating that the smaller enterprises -those with a lower turnover and a relatively young credit history that are most likely to resort to internal funds and operate with lower capital -were those mostly affected by the credit crunch, as they faced increasingly stringent credit constraints during the years of the financial crisis in Europe and their financial situation inevitably deteriorated (Castelli and Modina, 2010;Ferrando and Griesshaber, 2011;Dallago and Guglielmetti, 2012;Varum and Rocha, 2013).…”
Section: The Supply Of Credit In the Years Of Crisismentioning
confidence: 99%